Oxygen vacancies dynamics in redox-based interfaces: Tailoring the memristive response - Ferreyra, Cristian Daniel (2019)
Redox-based memristive devices are among the alternatives for the next generation of non-volatile memories, but also candidates to emulate the behavior of synapses in neuromorphic computing de- vices. Nowadays it is well established that the motion of oxygen vacancies at the nanoscale is the key mechanism to reversibly switch metal/insulator/metal structures from insulating to con- ducting, i.e. to accomplish the resistive switching effect. The control of oxygen vacancies dynamics has direct effects on the resistance changes, and therefore on different factors of memristive devices such as switching speed, retention, endurance or energy consumption. Advances in this direction demand not only experimental techniques that allow measuring oxygen vacancies profiles, but also theoretical studies that shed light on the involved mechanisms. Along these goals, we analize the oxygen vacancies dynamics in redox interfaces formed when an oxidizable metallic electrode is in contact with the insulating oxide. We show how the transfer of oxygen vacancies can be manipulated by using different electrical stimuli protocols that allow optimizing device figures such as ON/OFF ratio or writing energy dissipation. Analytical expressions for both high and low resistance states are derived in terms of total oxygen vacancies transferred at the interface. Our predictions are validated with experiments performed in Ti/La 1/3 Ca 2/3 MnO 3 redox memristive devices.